Kontruksi Nilai Kebangsaan dalam Pendidikan Pesantren Perspektif Buya Syafi’e Maarif - Nurhayati, Ifa; Roibin, Roibin; Karimah, Saidatul (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
The study of nationality and pesantren is always interesting because pesantren is a unique and unique model of education in Indonesia. On the privilege of pesantren, the question always arises whether pesantren accommodates national values and the educational process in it. How is the construction of national values in Islamic boarding school education. This question is the purpose of this research by using a library approach. Data analysis was done by content analysis. The results of the study indicate that the construction of national values in pesantren education should teach various tolerance values so that studies in the pesantren curriculum are taught knowledge of religions not only Islam. Both pesantren should instill equal citizenship by instilling the values of equality and justice. Third, human values should also be constructed in pesantren education